METROLOGICAL ASPECTS OF ENSURING MEASUREMENTS IN RAILWAY ROLLING STOCK PROJECTS (Transport systems and technologies, 2022)
The problems of obtaining reliable information in online mode about the technical condition of rolling stock are considered. It was determined that obtaining such information is possible thanks to the use of a system for monitoring the parameters of the condition of the rolling stock using technical means that carry out measurements based on metrological support.It is known that one of the main tasks of railway transport is the safety of traffic, which can be ensured by using a parameter monitoring system to maintain and restore the efficiency, reliability and reduce operational costs of rolling stock.The paper presents the metrological aspects of providing measurements of rolling stock parameters by the statistical method of calculating verification intervals, which allows to determine control errors based on the available initial data in the form of specified error intervals of measuring devices.A detailed description of the method and, accordingly, the results of using the method to determine the dependence of the average risk of verification and the dependence of the ratio of the value of the optimal control tolerance on the estimation of the error of the measuring device being verified to the limit of its permissible error on the ratio of losses due to false and undetected failures are presented, in a graphical form.
Keywords: metrological support, system, monitoring, rolling stock, method, means of measurement.